Depreciation and Rate Control: A Further Discussion - Bonbright, James C. (Quarterly Journal of Economics, 1916)
The problem of depreciation in retroactive regulation, 546. — Principle of replacement cost discussed, 547. — Absurdity of using replacement cost new, 549. — Objections to deduction of depreciation answered, 552. — Depreciation under the principle of original cost, 555.